2019
DOI: 10.1007/978-3-030-22629-9_20
|View full text |Cite
|
Sign up to set email alerts
|

On $$(1+\varepsilon )$$ -approximate Data Reduction for the Rural Postman Problem

Abstract: Given an undirected graph with edge weights and a subset R of its edges, the Rural Postman Problem (RPP) is to find a closed walk of minimum total weight containing all edges of R. We prove that RPP is WK[1]-complete parameterized by the number and cost d of edges traversed additionally to the required ones. Thus, in particular, RPP instances cannot be polynomial-time compressed to instances of size polynomial in d unless the polynomial-time hierarchy collapses. In contrast, denoting by b ≤ 2d the number of ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
(104 reference statements)
0
7
0
Order By: Relevance
“…Hence, we put forward the following: Can Theorem 2.1 be executed in quadratic, or even linear time? We remark that van Bevern et al [6] give a linear-time variant Theorem 2.1 for approximate kernelizations.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Hence, we put forward the following: Can Theorem 2.1 be executed in quadratic, or even linear time? We remark that van Bevern et al [6] give a linear-time variant Theorem 2.1 for approximate kernelizations.…”
Section: Discussionmentioning
confidence: 92%
“…Another direction, seemingly not addressed so far, aims on the running time. Note that Frank and Tardos [15] state no explicit running time of their algorithm, and Lenstra et al [20,Proposition 1.26] state that their simultaneous Diophantine approximation algorithm, which forms a subroutine in Frank and Tardos' technique, runs in O(d 6 (log( w ∞ )) O (1) ) time. Hence, we put forward the following: Can Theorem 2.1 be executed in quadratic, or even linear time?…”
Section: Discussionmentioning
confidence: 99%
“…We think that the approach taken by Reduction Rule 5.8, namely reducing all vertices that do not belong to some inclusion‐maximal set B of mutually sufficiently distant vertices, might be applicable to other metric graph problems: it ensures that, for each deleted vertex, some nearby representative in B is retained. In preliminary research, for example, we also found it to be applicable to a metric variant of the Min‐Power Symmetric Connectivity problem, where it is required to connect c disconnected parts of a wireless sensor network [4], and to the Location Rural Postman Problem [12]. Notably, this approach does not generalize well to asymmetric distances, so that another vexing question besides proving Conjecture 5.14 is whether the scheme for the parameter b + c presented in this work can be generalized to the directed Rural Postman Problem.…”
Section: Resultsmentioning
confidence: 99%
“…Since our main goal is evaluating the effect of our data reduction rather than the running time of our algorithm, we sacrificed speed for simplicity and implemented the part of our PSAKS described in Section 5.4.1 in approximately 200 lines of Python (not counting the testing environment) using the NetworkX library for finding minimum-weight perfect matchings, (bi)connected components, cut vertices, and spanning trees. 5 These routines are also contained in highly optimized C++ libraries like LEMON 6 and we expect that one could achieve a speedup by orders of magnitude by implementing our PSAKS in C++. We did not implement the weight reduction step described in Section 5.4.2, since it is mainly of theoretical interest (to prove a polynomial-size of the kernel rather than just a polynomial number of vertices and edges).…”
Section: Methodsmentioning
confidence: 99%
“…Pioneering work of Lokshtanov et al [LPRS17] on the approximate kernel is being followed by a series of papers generalizing/improving results mentioned in this work and establishing lossy kernels for various other problems. Lossy kernels for some variations of Connected Vertex Cover [EHR17, KMR18], Connected Feedback Vertex Set [Ram19], Steiner Tree [DFK + 18] and Dominating Set [EKM + 19, Sie17] have been established (also see [Man19,vBFT18]). Krithika et al [KMRT16] were first to study graph contraction problems from the lenses of lossy kernelization.…”
Section: Related Workmentioning
confidence: 99%